2022
DOI: 10.1136/tc-2022-057476
|View full text |Cite
|
Sign up to set email alerts
|

Removal of mango-flavoured Juul pods created opportunity for adulterated mango Juul-compatible pods with altered chemical constituents

Abstract: IntroductionJuul is a leading electronic cigarette (e-cigarette) brand in the USA. By November 2019, Juul pre-emptively limited online and in-store sales of non-tobacco or menthol-flavoured pods ahead of impending flavour bans. Since this removal, sale of mango-flavoured Juul-compatible pods was introduced to the market by smaller companies. The aim of this study was to compare chemical constituents of original Juul mango pods with mango-flavoured Juul-compatible pods.MethodsJuul and 16 brands of Juul-compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Due to variations in design and construction, these pods may modify the operation of original manufacturer devices, resulting in different nicotine and other toxicant emissions. Previous researchers found that the liquid used in prefilled aftermarket pods for JUUL contained greater numbers and concentrations of flavoring chemicals than the original pods, and that the maximum particulate yield per puff was 5.6 times higher for one aftermarket pod than JUUL …”
Section: Introductionmentioning
confidence: 98%
“…Due to variations in design and construction, these pods may modify the operation of original manufacturer devices, resulting in different nicotine and other toxicant emissions. Previous researchers found that the liquid used in prefilled aftermarket pods for JUUL contained greater numbers and concentrations of flavoring chemicals than the original pods, and that the maximum particulate yield per puff was 5.6 times higher for one aftermarket pod than JUUL …”
Section: Introductionmentioning
confidence: 98%